Effects of in vitro hyperthermia on the proliferative response of blood mononuclear cell subsets, and detection of interleukins 1 and 6, tumour necrosis factor-alpha and interferon-gamma. - Kappel, M (1991)
The role of endogenously mediated fever and exogenous hyperthermia as modulators of immune functions remains poorly understood. It is known that fever is mediated by several cytokines, including interleukin-1 alpha and interleukin-1 beta (IL-1 alpha and IL-1 beta), interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-alpha) and the interferons. The present communication examines the effect of exogenous hyperthermia on the detection of these cytokines and shows the suppressive effect of elevated temperature (39 degrees) on the amount of IL-1 beta, IL-6 and IFN-gamma (P less than 0.001) but not on IL-1 alpha and TNF-alpha concentrations. It is suggested that a negative feedback mechanism exists between temperature and the production of some of the molecules involved in the mediation of fever. It is known that hyperthermia increases the proliferative response of lymphocytes. We found a twofold increase in [3H]thymidine incorporation at 39 degrees compared to 37 degrees. The distribution of cells expressing CD3, CD4, CD8, CD14, CD16, CD19 and CD25 markers was the same at 37 degrees and 39 degrees.